Foreign Experience in Increasing the Attractiveness of Financial Statements - Anvar Ziyadullayevich Avlokulov; Makhmudova Sharifa Elmurodovna (Research Parks Publishers, 2022)
In the article given the procedure for drawing of the financial statements based on international standards, the possibility of analysis of the income statement and the prospects for their use in the practice of enterprises in Uzbekistan.